A street is a defile in a city” – the tactics of James Connolly - Pawłowska, Antonina (City and War, 2021)
The article analyses the influence of James Connolly – Irish socialist and the leader of the Irish Citizen Army – on the creation of strategy of the Easter Rising of 1916. The goal of the article is to compare the thesis put forward by Connolly in his essays discussing the issues related to street fighting by the example of various armed conflicts with the plan of the Easter Rising and its execution in April of 1916. The sources for this analysis were his political writings and speeches, as well as testimonies of his associates from the collection of the Irish Bureau of Military History.